Penggunaan Kosakata Informal dalam Kolom Komentar Akun Tiktok @Iniganta - Ayunda, Putri; Ermanto, Ermanto (Universitas Negeri Padang, 2024)
This study aims to (1) explain the form of informal vocabulary in the comment column of the Tiktok account @iniganta, (2) explain the morphological process of informal vocabulary in the comment column of the Tiktok account @iniganta, (3) explain the origin of informal vocabulary language in the comment column of the Tiktok account @iniganta. This research is qualitative research using a descriptive method. The results of this study are First, informal vocabulary in the comment column of the Tiktok account @iniganta found as many as 1634 data which includes, basic words found as many as 1262 data and derived words found as many as 372 data; Second, based on the morphological process, 372 data were found which included, (1) affixation found as many as 168 data, (2) acronymization found as many as 159 data, (3) composition found as many as 38 data, (4) reduplication found as many as 7 data, and (5) conversion was not found in the comment column of the Tiktok account @iniganta. Third, based on the origin of the language, three types of languages were found, including, (1) Indonesian found as many as 1167 data, (2) regional languages found as many as 138 data, and (3) foreign languages found as many as 329 data. Of the three types of languages that have been mentioned, the most dominant language used in the comment column of @iniganta Tiktok account is Indonesian.